Association of lifetime lactation and characteristics of menopause: a longitudinal cohort study - Natalie V. Scime; Beili Huang; Meredith Merilee Brockway; Hilary K. Brown; Erin A. Brennand (BMC, 2024)
Abstract Background Lactation has many established benefits for women's long-term health; however, its influence on menopause is less clear. This study investigated the association between lifetime duration of lactation and the timing and type of menopause in midlife women. Methods We analyzed survey data on 19,783 parous women aged 40 to 65 years at enrollment in the Alberta's Tomorrow Project (2000-2022), a prospective community-based cohort study in Alberta, Canada. Duration of lifetime lactation across all births was categorized as: <1 month (reference group; 19.8% of women), 1-3 months (12.1%), 4-6 months (11.7%), 7-12 months (18.8%), and ≥ 13 months (37.7%). Women were classified as premenopause, natural menopause (age at 1 year after the final menstrual period), surgical menopause (age at bilateral oophorectomy), or indeterminate menopause (age at premenopausal hysterectomy with ovarian preservation). Flexible parametric survival analysis and multinomial logistic regression were used to analyze menopause timing and type, respectively, according to lactation status and controlling for birth year, education, parity, hormonal contraceptive use, and smoking. Results In a dose-response manner, longer lactation was associated with reduced risk of natural menopause before age 50 (for ≥ 13 months of lactation, adjusted hazard ratio at age 45: 0.68, 95% CI 0.59-0.78), surgical menopause before age 55 (age 45: 0.56, 0.50-0.63), and indeterminate menopause before age 50 (age 45: 0.75, 0.69-0.82). Longer lactation was associated with lower odds of surgical (adjusted odds ratio 0.54, 95% CI 0.45-0.66) and indeterminate menopause (0.63, 0.55-0.73), compared to natural menopause. Conclusions Optimizing the timing of natural menopause and reducing risks of early surgical and indeterminate menopause may be novel maternal benefits of breastfeeding.